Analysis of the effect of inflation, economic growth, and investment on unemployment in the province of Central Java - Artriyan Syahnur Tirta (Institute of Accounting Research and Novation (IARN), 2022)
The object of this research was carried out in all regencies/cities in Central Java in the 2008-2010 period. The data used in this study is secondary data obtained from the Central Bureau of Statistics and the Regional Investment Board of Central Java Province. The data analysis technique used is panel data regression analysis and path analysis using the help of the Eviwes 6.0 computer program using panel data (time series and cross section). Based on the results of data analysis, it shows that 1) the inflation variable has a negative and significant effect on unemployment, namely 0.031815, 2) the economic growth variable has a negative and significant effect on unemployment, namely 0.116828, 3) the investment variable has a negative and significant effect on unemployment, namely 0.208683. Based on the results of the research above, it can be concluded that there is an influence between inflation, economic growth, and investment on unemployment in Central Java Province. The suggestion in this study is that as an effort to overcome unemployment, the government is expected to be able to maintain inflation rate stability with fiscal policy in the form of government spending on sectors that have the potential to absorb labor and increase quality economic growth. In addition, it is hoped that the Government can attract investors by creating a conducive investment climate and facilitating the licensing process so that jobs will increase and be able to absorb unemployment.